Pragmatic Study of Illocutionary Speech Acts in the Short Story Shoriul Hasad by Taha Husein - Kusumowardani, Hanifah Lintang (CV. Rayyan Dwi Bharata, 2023)
As social creatures, humans cannot be separated from speaking activities. In speaking activities, the speech that occurs between the speaker and the interlocutor is not just about saying something, but is also used to carry out an action. Illocutionary speech acts not only occur in everyday communication, but in short story literary works which are depictions of life, there are also illocutionary speech acts in speech between characters. Illocutionary speech acts play a very important role in conveying the message in the short story to the readers. The author chose the short story Shoriul Hasad by Taha Husein as the research object because the author was interested in how illocutionary speech acts were in the speech spoken by the characters in the short story. The method used in this research is a descriptive analysis method, namely describing the found facts in the form of analysis. This research is included in library research where all data sources are written and obtained through various literature sources related to the research. Based on the results of the analysis, it can be concluded that in the short story Shoriul Hasad by Taha Husein, 14 sentences were found which are illocutionary speech acts in the form of representative, directive, expressive and commissive. Illocutionary speech acts in representative form consist of 2 sentences which are utterances to tell something. Illocutionary speech acts in the form of directives consist of 6 sentences consisting of 1 prohibiting utterance, 3 requesting utterances, 1 commanding utterance, 1 advising utterance. Illocutionary speech acts in expressive form consist of 5 sentences consisting of 2 utterances showing liking and 3 utterances showing dislike. The commissive illocutionary speech act consists of 1 sentence which is 1 threat utterance.